Productive Performance of Brachiaria brizantha cv. Paiaguás in Response to Different Inoculation Techniques of Azospirillum brasilense Associated with Nitrogen Fertilization in the Brazilian Amazon - Gianna Maria Oscar Bezerra; Cleyton de Souza Batista; Daryel Henrique Abreu de Queluz; Gabriela de Jesus Coelho; Daiane de Cinque Mariano; Pedro Henrique Oliveira Simões; Perlon Maia dos Santos; Ismael de Jesus Matos Viégas; Ricardo Shigueru Okumura; Raylon Pereira Maciel (Nitrogen, 2025)
With the increase in prices of correctives and fertilizers, the investigation of the interactions between plants and plant growth-promoting bacteria shows an economically viable and sustainable alternative, and the use of Azospirillum brasilense has shown an increase in efficiency of nitrogen use and increased pasture yield. This study, conducted in the Brazilian Amazon, aimed to evaluate the effect of different inoculation techniques of Azospirillum brasilense associated with the dose of nitrogen topdressing on the productive performance of Brachiaria brizantha cv. Paiaguás is a grass species commonly cultivated in this region. The experiment was conducted in the Experimental Forage Sector of the Federal Rural University of the Amazon, Parauapebas city, Brazil. The experimental design was a randomized block design in a 3 × 3 factorial arrangement, with three inoculation methods (control, seed, and foliar) and three nitrogen fertilization doses (0, 75, and 150 kg ha−1 of N), with four replicates. An effect was observed in interaction between inoculation and nitrogen fertilization (p ≤ 0.05) for the variables total forage green mass, total forage dry mass, dry mass of leaf blade, dry stem mass, and number of tillers m−2. The dose of 150 kg ha−1 of N promoted a positive effect of N on the total forage dry mass and LAI (leaf area index). Inoculation with Azospirillum brasilense, especially foliar application, efficiently increased Brachiaria brizantha cv. Paiaguás yield, potentially reducing the use of nitrogen fertilizers, promotes greater sustainability in pasture management.